1996
DOI: 10.1046/j.1365-2141.1996.d01-1839.x
|View full text |Cite
|
Sign up to set email alerts
|

Diamond‐Blackfan anaemia in the U.K.: analysis of 80 cases from a 20‐year birth cohort

Abstract: The U.K. Diamond-Blackfan Anaemia (DBA) Registry was established with the aim of providing a representative database for studies on the aetiology, pathophysiology and treatment of DBA. We have analysed retrospective data from 80 cases (33 male, 47 female) born in the U.K. in a 20-year period (1975-94), representing an annual incidence of 5 per million live births. Ten children from seven families had an apparently familial disorder. 13% were anaemic at birth, and 72.5% had presented by the age of 3 months. 67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
2
7

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 23 publications
(25 reference statements)
6
123
2
7
Order By: Relevance
“…While this is still true, it is now clear that poor steroid sensitivity is common to all patients with RPS19 alterations. Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006].…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
See 4 more Smart Citations
“…While this is still true, it is now clear that poor steroid sensitivity is common to all patients with RPS19 alterations. Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006].…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
“…Their response to the first steroid course is 46% (42/91 patients whose data were available, two of them showing a partial response) compared with more than 70% of the overall DBA population [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Over the last 10 years, clinical data from the main European and North American DBA registries have been published [Ball et al, 1996;Willig et al, 1999b;Campagnoli et al, 2004;Lipton et al, 2006]. Our review of these reports with data for over 800 DBA patients has shown that those with RPS19 mutations display a significantly lower sensitivity to steroids (po0.0001) and are significantly more likely to become transfusion dependent or require SCT (po0.0001) ( Table 2).…”
Section: Genotype^phenotype Correlationmentioning
confidence: 99%
See 3 more Smart Citations